The association of small bombs - Mahajan, Karan (Penguin Books, 2016)
When brothers Tushar and Nakul Khurana, two Delhi schoolboys, pick up their familys television set at a repair shop with their friend Mansoor Ahmed one day in 1996, disaster strikes without warning. A bombone of the many "small" bombs that go off seemingly unheralded across the worlddetonates in the Delhi marketplace, instantly claiming the lives of the Khurana boys, to the devastation of their parents. Mansoor survives, bearing the physical and psychological effects of the bomb. After a brief stint at university in America, Mansoor returns to Delhi, where his life becomes entangled with the mysterious and charismatic Ayub, a fearless young activist whose own allegiances and beliefs are more malleable than Mansoor could imagine. Woven among the story of the Khuranas and the Ahmeds is the gripping tale of Shockie, a Kashmiri bomb maker who has forsaken his own life for the independence of his homeland. Karan Mahajan writes brilliantly about the effects of terrorism on victims and perpetrators, proving himself to be one of the most provocative and dynamic novelists of his generation. -- Provided by publisher.